2004
DOI: 10.1289/ehp.6590
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic and estrogenic activity in water bodies receiving cattle feedlot effluent in Eastern Nebraska, USA.

Abstract: Studies reveal that surface waters worldwide are contaminated with hormonally active agents, many released from sewage treatment plants. Another potential source of aquatic hormonal contamination is livestock feedlot effluent. In this study, we assessed whether feedlot effluent contaminates watercourses by measuring a) total androgenic [methyltrienolone (R1881) equivalents] and estrogenic (17β-estradiol equivalents) activity using the A-SCREEN and E-SCREEN bioassays and b) concentrations of anabolic agents via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
4
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(173 citation statements)
references
References 43 publications
6
160
4
3
Order By: Relevance
“…For example, the HSI increase observed, could be linked to implication of liver in VTG synthesis at REV, ESC and RHO and/or to the role of this organ in detoxification process. In a same manner, GSI could be increased follow the exposure to contaminant able to disturb reproductive cycle as previously reported in fish exposed to a variety of endocrinemodulating substances (Orlando et al, 2004). For example, estrogens could be implicated at REV where VTG was induced, however, but other compounds could explain the increase in GSI noticed at VIL where endocrine disruption biomarker were not present.…”
Section: Individual Effects In Contaminated Sitessupporting
confidence: 70%
See 1 more Smart Citation
“…For example, the HSI increase observed, could be linked to implication of liver in VTG synthesis at REV, ESC and RHO and/or to the role of this organ in detoxification process. In a same manner, GSI could be increased follow the exposure to contaminant able to disturb reproductive cycle as previously reported in fish exposed to a variety of endocrinemodulating substances (Orlando et al, 2004). For example, estrogens could be implicated at REV where VTG was induced, however, but other compounds could explain the increase in GSI noticed at VIL where endocrine disruption biomarker were not present.…”
Section: Individual Effects In Contaminated Sitessupporting
confidence: 70%
“…The increases of spiggin content in fish from ESC and RHO suggested that these fish were exposed to androgenic compounds. Surface water contamination by this class of endocrine disrupters is very little documented (Blankvoort et al, 2005;Soto et al, 2004) with the exception of pulp mill effluents that have an well-known masculinising effect (Cody and Bortone, 1997;Denton et al, 1985;Howell and Denton, 1989). Recently, Blankvoort et al (2005) reported contamination of European rivers by many androgens including testosterone and its metabolites, 17α-methyltestosterone or trenbolone, that were probably released in aquatic ecosystems by sewage treatment plants and industrial activities, and that could induce spiggin in female sticklebacks.…”
Section: Individual Effects In Contaminated Sitesmentioning
confidence: 99%
“…This is consistent with the general water quality classification of the three rivers. The estrogenic activities detected in surface water and sediment of the Shijing River were approximately one to two orders of magnitude higher than those reported in Korea [32], Portugal [33], the United Kingdom [34], and the United States [35], where the estrogenic activities ranged from below the limit of detection to 4.01 ng EEQ/L in surface water and from below the limit of detection to 12.1 ng EEQ/g in sediment. The estrogenic activities in the rivers of other regions clearly fall in the range for the Liuxi and Zhujiang rivers.…”
Section: Discussioncontrasting
confidence: 55%
“…This suggests that some unknown chemicals might contribute to the estrogenicity of the samples (Sarmah et al, 2006;Soto et al, 2004;Viganò et al, 2008).…”
Section: Comparison Of Estrogenicity By Yes Bioassay and Chemical Anamentioning
confidence: 98%